1992
DOI: 10.1073/pnas.89.4.1383
|View full text |Cite
|
Sign up to set email alerts
|

Mouse model of neurodegeneration: atrophy of basal forebrain cholinergic neurons in trisomy 16 transplants.

Abstract: Vulnerability of specific brain regions and neuronal populations is a characteristic feature of Alzheimer disease and Down syndrome. Cholinergic neurons of the basal forebrain degenerate in both disorders. The basis for neuronal degeneration is unknown. Mouse trisomy 16 (Ts 16) is an animal model of Down syndrome. We sought an experimental system in which the survival and development of Ts 16 basal forebrain cholinergic neurons could be examined beyond the fetal period. As Ts 16 mice do not survive birth, we t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Previous studies have shown that Ts65Dn mice exhibit selective age-dependent atrophy of BFCNs, a progressive decline in numbers of cholinergic neurons in the basal forebrain detected by established cholinergic marker proteins, and astrocytic hypertrophy [18,31,40,41]. The present study combined quantitative MRI and immunocytochemical and enzyme histochemical studies to demonstrate that the loss of cholinergic neurons in Ts65Dn mice is selective for a specific subgroup of cholinergic neurons localized to the MSN and to a lesser degree, the NB.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have shown that Ts65Dn mice exhibit selective age-dependent atrophy of BFCNs, a progressive decline in numbers of cholinergic neurons in the basal forebrain detected by established cholinergic marker proteins, and astrocytic hypertrophy [18,31,40,41]. The present study combined quantitative MRI and immunocytochemical and enzyme histochemical studies to demonstrate that the loss of cholinergic neurons in Ts65Dn mice is selective for a specific subgroup of cholinergic neurons localized to the MSN and to a lesser degree, the NB.…”
Section: Discussionmentioning
confidence: 93%
“…One of the most marked pathologic changes in the brain in Alzheimer disease is the degeneration of this cholinergic projection and the consequent reduction in the number of nAChRs (Dumas and Newhouse, 2011;Pinto et al, 2011). A number of studies have found that the b-amyloid (Ab) peptide (a hallmark of Alzheimer disease) plays a critical role in neuronal degeneration and subsequent memory deficits (Price et al, 1985;Holtzman et al, 1992;Wenk, 1993;Fraser et al, 1997;Capsoni et al, 2000;Dolga et al, 2009). Furthermore, a recent electrophysiological study has demonstrated that Ab binds with higher affinity to a 7 b 2 -nAChR than to a 7 -nAChR, and that this can produce hippocampal neuronal hyperexcitation (through a 7 -nAChR upregulation) and subsequent neurodegeneration (Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For trkA expression studies, eight animals were used for in situ hybridization histochemistry (ISHH) and eight for immunocytochemistry. Rats were deeply anesthetized (Holtzman et al, 1992a) and perfused transcardially with 60 ml of PBS (pH 7.4, 4°C) followed by 200 ml of 4% (wt/vol) paraformaldehyde in 0. I M sodium phosphate (pH 7.4, 4°C).…”
Section: Methodsmentioning
confidence: 99%
“…Sixteen adult female Sprague-Dawley rats were anesthetized (Holtzman et al, 1992a) and brains were removed and placed in cold PBS (pH 7.4, 4°C). The septal region was dissected as described (Johnston et al, 1987).…”
Section: Methodsmentioning
confidence: 99%